Feasibility of potable water generators to meet vessel numeric ballast water discharge limits. Issue 1 (15th July 2017) - Albert, Ryan J.; Viveiros, Edward; Falatko, Debra S.; Tamburri, Mario N.
Abstract: Ballast water is taken on-board vessels into ballast water tanks to maintain vessel draft, buoyancy, and stability. Unmanaged ballast water contains aquatic organisms that, when transported and discharged to non-native waters, may establish as invasive species. Technologies capable of achieving regulatory limits designed to decrease the likelihood of invasion include onboard ballast water management systems. However, to date, the treatment development and manufacturing marketplace is limited to large vessels with substantial ballast requirements. For smaller vessels or vessels with reduced ballast requirements, we evaluated the feasibility of meeting the discharge limits by generating ballast water using onboard potable water generators. Case studies and parametric analyses demonstrated the architectural feasibility of installing potable water generators onboard actual vessels with minimal impacts for most vessel types evaluated. Furthermore, land-based testing of a potable water generator demonstrated capability to meet current numeric discharge limits for living organisms in all size classes. Graphical abstract: Highlights: Untreated ballast water from vessels can transport and introduce invasive species. We evaluate ballast water treatment using potable water generators (PWGs). Engineering and parametric analyses show PWG use is feasible for many small vessels. Land-based testing shows a PWG removing living organisms below regulatory limits. The PWG produced extremely low residual toxicity in discharged ballast water.